Expedited soil–water characteristic curve tests using combined centrifuge and chilled mirror techniques - Rahardjo, Harianto (2018)
A soil–water characteristic curve (SWCC) shows soil’s ability to provide water availability and the rate that this water can be transmitted and replenished. However, the current commonly used method to determine the SWCCs of soils (the axis-translation method) is time consuming. This study combines two relatively new but established methods (centrifuge and chilled mirror psychrometer) to find a rapid and reliable way to obtain the SWCC for a large range of suctions. For comparison, the SWCC was also independently measured using the axis-translation method (Tempe cell and pressure plate). The comparisons show that the SWCC parameters (air-entry values, residual suctions, and slope of SWCC) determined using the combined centrifuge and chilled mirror psychrometer methods agree well with the same SWCC parameters determined using the Tempe cell and pressure plate methods (axis-translation method). At the same time, the time taken was cut down from a few months for the axis-translation method to about two days for the combined centrifuge and chilled mirror psychrometer.